PENGARUH PERSONAL SELLING TERHADAP PENCAPAIAN TARGET PENJUALAN (STUDI KASUS PT. SETIAWAN SEDJATI) - Ranty Octavianita; Eki Dudi Darmawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The existence of instability in the value of sales is an important evaluation that must be carried out by management. The purpose of this study is to determine the effect of Personal Selling on Sales Targets at PT. Setiawan Sedjati. The location of data collection is done at PT. Setiawan Sedjati Bandung. The research method uses quantitative methods. This research is a descriptive correlation with sample data collection using the Slovin formula. A total of 67 respondents were used as samples in this study consisting of employees of the marketing division and customers of PT. Setiawan Sedjati. The existing samples were then processed using SPSS Statistic Software version 26. Based on the processed data, the results of the regression equation Y = 20.478 + 0.182x. Then the correlation coefficient value of 0.747, it can be said that these results have a strong relationship between variables. The value of the coefficient of determination is 55.8%. The calculated value of 9.068 > 2.6512 this result shows a significant increase between variables on the t-test. It can be concluded that H1 accepted and H0 rejected, namely the variable personal selling. The variable personal selling has an influence on sales.